Postnatal Involution and Counter-Involution of the Thymus - Cowan, Jennifer E.; Takahama, Yousuke; Bhandoola, Avinash; Ohigashi, Izumi (Frontiers in Immunology, 2020)
Thymus involution occurs in all vertebrates. It is thought to impact on immune responses in the aged, and in other clinical circumstances such as bone marrow transplantation. Determinants of thymus growth and size are beginning to be identified. Ectopic expression of factors like cyclin D1 and Myc in thymic epithelial cells (TEC)s results in considerable increase in thymus size. These models provide useful experimental tools that allow thymus function to be understood. In future, understanding TEC-specific controllers of growth will provide new approaches to thymus regeneration.